Maternal socioemotional investment in children and their adjustment to nursery - Velikić, Dejana; Filipović, Bojana; Bačić, Jovana; Bogosanović, Bojana (Primenjena psihologija, 2010)
Childs adjustment to nursery is influenced by a numeber of factors, among which the most significant is the quality of caregiving, and parent-child relation. In this paper, the quality of care and mother-child relations was defined by four factors: satisfaction in parenting, sensitivity, responsiveness and knowledge, acceptance of the child and the role of parents and separation anxiety, which together define a construct of maternal socioemotional investment in children. The total sample consisted of 316 infants, first time starting the nursery. Their adjustment was assessed by the their nursery teachers after a period of adaptation. Results indicate that maternal socioemotional investment, especially maternal sensitivity and parenting role acceptance, is significant factor influencing adjustment in infancy.